دور التكنولوجيا المالية في تحسين أداء البنوك التجارية دراسة ميدانية لعينة من وكالات البنوك التجارية بولاية الوادي - طواهرية سارة; اسماعيلية ايناس; عثماني نصيرة (جامعة الوادي University Of Eloued, 2025)
"هدفت هذه الدراسة إلى معرفة دور التكنولوجيا المالية في تحسين أداء البنوك التجارية، وذلك بدراسة ميدانية لعينة من وكالات البنوك بالوادي، ومن أجل بلوغ هذا الهدف تم الاعتماد على المنهج الوصفي في الفصل النظري، حيث تطرقنا نظريا للتكنولوجيا المالية والأداء البنكي، كما تم الاعتماد على المنهج التحليلي في دراسة الحالة من خلال الإعتماد على تحليل الاستبيان وعلى برنامج ""SPSS.V27"" في تحليل النتائج. تم التوصل إلى وجود تأثير معنوي ذو دلالة إحصائية للتكنولوجيا المالية بجميع أبعادها في تحسين أداء البنوك محل الدراسة بولاية الوادي عند مستوى الدلالة (α≤ 005)؛ كما توصلنا إلى أن التكنولوجيا المالية تلعب دورًا مهمًا ومباشرًا في تحسين الأداء المالي للبنوك محل الدراسة خاصة والبنوك التجارية عامة. This study aimed to explore the role of financial technology in improving the performance of commercial banks, through a field study of a sample of bank branches in El Oued. To achieve this goal, the descriptive approach was adopted in the theoretical chapter, which theoretically addressed financial technology and banking performance. The analytical approach was also adopted in the case study, relying on questionnaire analysis and SPSS.V27 to analyze the results. The study found a statistically significant effect of financial technology in all its dimensions on improving the performance of the banks under study in El Oued Province at the significance level (α≤0.05). We also concluded that financial technology plays an important and direct role in improving the financial performance of the banks under study in particular and commercial banks in general.
Keywords: بنوك تجارية؛; تكنولوجيا مالية; خدمات مالية مفتوحة; أداء مالي; أداء اقتصادي; أداء تسويقي; أداء استراتيجي؛ تحول رقمي; Commercial banks; financial technology; open financial services; financial performance; economic performance; marketing performance; strategic performance; digital transformation.